2012
DOI: 10.1080/15350770.2012.673974
|View full text |Cite
|
Sign up to set email alerts
|

Oral History: A Pragmatic Approach to Improving Life Satisfaction of Elders

Abstract: This study evaluated the impact of oral history interviews on life satisfaction of older adults who were interviewed by college students enrolled in a gerontology course. Using an experimental, pretest-posttest design, baseline life satisfaction scores of elders in the intervention group were compared to those in the control group immediately following three one-hour oral history interviews (posttest) and again 10 weeks later (retest). At posttest, no differences in life satisfaction were found between groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…A study found that life satisfaction was affected by many dimensions, including lifestyle and family relationships ( 64 ). Therefore, it may take longer to observe an improvement in life satisfaction among older adults, which was consistent with our results ( 16 , 27 ). However, there is no evidence of a significant correlation between the duration of each intervention and the effectiveness of the outcome.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A study found that life satisfaction was affected by many dimensions, including lifestyle and family relationships ( 64 ). Therefore, it may take longer to observe an improvement in life satisfaction among older adults, which was consistent with our results ( 16 , 27 ). However, there is no evidence of a significant correlation between the duration of each intervention and the effectiveness of the outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Of the seven studies on life satisfaction, six used group sessions, which showed significant statistical significance compared with individual reminiscence ( P < 0.01). The only study that used individual sessions did not significantly improve life satisfaction ( 27 ). In addition, of the twelve studies on depression symptoms, ten used group sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, that study differed from ours in that it involved severely depressed older adults who were on psychiatric medication. Our research aligns with the studies conducted by Ligon et al [41] and Chan et al [20], which investigated verbal reminiscence therapy's effects on older adults' well-being using a design that included initial, subsequent, and follow-up evaluations. The findings revealed that the differences between the control and experimental groups became statistically significant after 10 weeks.…”
Section: Discussionsupporting
confidence: 77%
“…This process may enhance the participant’s general well-being, which may help reduce their loneliness [ 20 ]. We found that making a life-story book influenced depression and life satisfaction, which enhanced the QoL of the intervention group participants, perhaps because of the cumulative benefits of this activity [ 16 , 41 ]. Life-story work promotes attributing meaning to one’s life cycle, enhancing a sense of purpose and fulfillment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%